0069 A preliminary examination of swine caretakers' perspectives for euthanasia technology and training. (1st October 2016) - McGee, M.; Parsons, R. L.; O'Connor, A. M.; Johnson, A. K.; Anthony, R.; Ramirez, A.; Millman, S. T.
Abstract: An observational study was performed to better understand swine caretaker attitudes and opinions about euthanasia methods in swine production. A questionnaire was developed for swine caretakers to document the following: (1) psychosocial aspects, such as moral stress and job satisfaction associated with euthanasia, (2) current use of euthanasia techniques, and (3) views on animal welfare. To gain insight on caretakers' perspectives on the issues listed above, caretakers were asked to rank their personal opinions on these topics. A total of 2104 surveys were mailed between December 2014 and June 2015 to caretakers associated with four swine production companies in eight states. The return rate was 8.3% ( n = 175), with 168 completed surveys used for analysis. Respondents included 115 male and 53 female caretakers, whose work experiences with pigs ranged from <1 to 55 yr. Sixty-seven percent of caretakers worked in swine breeding units, while the remainder worked in farrowing, nursery, grow finish units, or a combination of production cycle units. Odds ratio analyses were performed to examine the effects of gender on caretaker opinion and acceptance regarding euthanasia techniques. There were no differences between male and female caretakers regarding the acceptance of different euthanasia methods in suckling pigs ( P > 0.05). A large percentage of caretakers agreed that it is important to have good skills for euthanasia, that they knew how to euthanize humanely, and that it is more humane to euthanize terminally ill pigs than to let them die (93, 95, and 95%, respectively). Male and female caretakers did not differ in their personal opinions about euthanizing pigs, speaking publicly about their job, or euthanasia preferences ( P > 0.05). Forty-nine percent of caretakers were trained in euthanasia techniques within the last year, and 30% reported that they would like more training. Caretakers preferred to be trained on-farm, followed by the use of video, classroom setting with a trainer, and reading materials. Caretakers rated carbon dioxide more acceptable than the use of blunt force trauma for suckling pigs (70% and 37%, respectively). The current study suggests that swine caretakers agree that proper euthanasia techniques are important and male and female caretakers do not differ in perspectives concerning euthanasia technology and training.